Anterior Iliopsoas Impingement due to a Malpositioned Acetabular Component - Effective Relief by Surgical Cup Reorientation. Issue 2 (March 2017) - Schoof, Benjamin; Jakobs, Oliver; Schmidl, Stefan; Lausmann, Christian; Fensky, Florian; Beckmann, Johannes; Gehrke, Thorsten; Gebauer, Matthias
Background: Determining the aetiology of persistent pain following total hip arthroplasty (THA) can be challenging. Impingement of the iliopsoas muscle due to a malpositioned acetabular component after THA might be a potential cause of postoperative groin pain. Methods: We retrospectively analysed the data of 12 consecutive patients from our orthopaedic department who underwent cup revision for painful iliopsoas impingement after primary THA. Results: Thorough physical examination as well as radiological assessment of the included patients revealed that malpositioning of the acetabular component provoked iliopsoas impingement. The Harris Hip Score and the orientation of the acetabular component before and after surgical revision at an average follow-up of 56 months were analysed. Conclusions: We were able to demonstrate that surgical cup revision and reorientation resulted in distinctly improved scores and is a feasible option to effectively treat persistent iliopsoas impingement due to a malpositioned acetabular component following THA.